High-performance foam thermal insulation material and method for preparing the same

CN122810433APending Publication Date: 2026-09-25SHANDONG JISHUN ENERGY SAVING BUILDING MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610474193.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-04-11
Publication Date
2026-09-25

AI Technical Summary

Technical Problem

[0004]传统型的发泡聚苯乙烯是以戊烷为发泡剂,采用这种有机发泡剂的主要缺点是在聚合物材料的加工及使用过程中,低沸点的戊烷非常容易挥发到大气中,从而对我们人类赖以生存的环境造成污染,不符合当前的绿色环保要求

Benefits of technology

[0033]本发明公开了一种高性能泡沫保温材料及其制备方法,先将苯乙烯单体和引发剂加入分散剂水溶液中,接着加入发泡剂,搅拌混匀,得到预混液;然后对预混液进行加热处理,搅拌降温至35~40℃,停止搅拌,过滤取固体,水洗,得到可发性聚苯乙烯珠粒;最后对可发性聚苯乙烯珠粒进行蒸汽加热预发泡,熟化,模具成型,脱模,即得。本发明制备方法简单,通过特定无机发泡剂的使用,提高泡沫保温材料性能。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application discloses a kind of high-performance foam thermal insulation material and preparation method thereof, first styrene monomer and initiator are added into dispersant aqueous solution, then foaming agent is added, stirring is uniformly obtained, and premix liquid is obtained;Then the premix liquid is heated, and the temperature is reduced to 35-40 DEG C by stirring, stops stirring, and the solid is filtered, washed with water, and obtainable expandable polystyrene beads;Finally, the expandable polystyrene beads are steam heated, prefoamed, cured, molded, demoulded, and obtained.The preparation method is simple, and the performance of the foam thermal insulation material is improved by using a specific inorganic foaming agent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a high-performance foam insulation material and its preparation method. It belongs to the field of insulation material processing technology. Background Technology

[0002] With social development and the improvement of people's living standards, people have increasingly higher requirements for building energy consumption and environmental protection, and have placed higher demands on the thermal insulation performance of buildings. The emergence of building insulation materials meets this requirement, making indoor spaces warm in winter and cool in summer, and greatly reducing indoor heating and cooling energy consumption.

[0003] Polystyrene is one of the world's most produced plastics, a polymer synthesized from styrene monomers through a free radical addition polymerization reaction. Polystyrene foam insulation boards are building insulation materials made from polystyrene resin, and are divided into two categories: molded polystyrene (EPS) boards and extruded polystyrene (XPS) boards. They are widely used in wall insulation, roof insulation, underfloor heating, and highway construction. EPS boards are molded from pre-expanded beads, featuring a closed-cell structure, and are mostly used for conventional building insulation and packaging. XPS boards are formed using an extrusion process to create a uniform honeycomb structure, resulting in low thermal conductivity, high compressive strength, and low water absorption. They also possess moisture-proof and corrosion-resistant properties, making them suitable for heavy-duty applications such as airport runways and long-term insulation projects, with a long service life. XPS has advantages in compressive strength, service life, and stability, while EPS is less expensive due to its flexible manufacturing process.

[0004] Traditional expanded polystyrene uses pentane as a blowing agent. The main drawback of using this organic blowing agent is that during the processing and use of polymer materials, the low-boiling-point pentane is very easy to volatilize into the atmosphere, thereby polluting the environment on which we humans depend for survival, which does not meet the current requirements for green environmental protection. Summary of the Invention

[0005] The purpose of this invention is to overcome the shortcomings of the prior art and provide a high-performance foam insulation material and its preparation method.

[0006] To achieve the above objectives, the present invention adopts the following technical solution:

[0007] A method for preparing a high-performance foam insulation material includes the following steps:

[0008] (1) First, add styrene monomer and initiator to the dispersant aqueous solution, then add foaming agent, stir and mix well to obtain premixed liquid;

[0009] (2) Then heat the premixed liquid, stir and cool it down to 35-40°C, stop stirring, filter to take the solid, wash with water, and obtain expandable polystyrene beads.

[0010] (3) Finally, the expandable polystyrene beads are pre-foamed by steam heating, cured, molded, and demolded to obtain the foam insulation material.

[0011] The foaming agent is prepared as follows: first, a nano zinc oxide sol is prepared using zinc salt and polyethylene glycol 400 as raw materials; then, mesoporous zinc oxide is added to the nano zinc oxide sol and stirred until homogeneous to obtain a premix; then, the nano zinc oxide graphene composite material is surface-treated sequentially with tetraethyl orthosilicate ethanol solution and 3-aminopropyltrihydroxysilane to obtain a surface-modified composite material; finally, the surface-modified composite material and bicarbonate are added to the premix and stirred until homogeneous.

[0012] Preferably, the preparation method of the nano zinc oxide sol is as follows: add zinc salt to polyethylene glycol 400, heat at 180-200°C for 30-40 minutes, cool naturally to 30-40°C, centrifuge and collect the supernatant to obtain the sol; wherein, the ratio of zinc salt to polyethylene glycol 400 is 2-3 mmol: 40-50 mL, and the zinc salt is zinc chloride or zinc nitrate.

[0013] Preferably, the mass ratio of nano zinc oxide sol, mesoporous zinc oxide, surface-modified composite material, and bicarbonate is 10:2-3:2-3:3-4; the bicarbonate is selected from any one or more of sodium bicarbonate, potassium bicarbonate, and ammonium bicarbonate.

[0014] Preferably, the mesoporous zinc oxide is prepared by the following method: P123 (polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer) is first dispersed in an aqueous ethanol solution with a volume concentration of 70-80%, then zinc chloride and triethanolamine are added, and the mixture is stirred for 6-7 hours. The mixture is then transferred to a reaction vessel and subjected to hydrothermal reaction at 100-120°C for 12-15 hours. The precipitate is collected by centrifugation, washed with water, and dried to obtain the final product.

[0015] More preferably, the ratio of P123, aqueous ethanol solution, zinc chloride, and triethanolamine is 0.3–0.4 mmol: 100 mL: 0.3–0.4 mmol: 0.5–0.6 mL.

[0016] Preferably, the nano-zinc oxide graphene composite material is prepared by the following method: First, an aqueous solution of graphene oxide and an aqueous solution of vitamin C are mixed evenly and heated at 80-90°C for 3-4 hours to achieve gelation, and the wet gel is collected; then, the wet gel is soaked in distilled water to remove residual vitamin C aqueous solution, and then freeze-dried under vacuum to obtain an aerogel; then, sodium hydroxide solution is added dropwise to zinc acetate solution, stirred and mixed evenly, and vacuum filtered to obtain zinc hydroxide powder, which is then heat-treated to obtain nano-zinc oxide powder; finally, the aerogel and nano-zinc oxide powder are transferred to a tube furnace and calcined at high temperature under a nitrogen atmosphere to obtain the final product.

[0017] Further preferably, the volume ratio of the graphene oxide aqueous solution to the vitamin C aqueous solution is 1.5 to 2:1, and their concentrations are 2 mg / mL and 100 mg / mL, respectively; the volume ratio of the zinc acetate solution to the sodium hydroxide solution is 1:1.8 to 2, and their concentrations are 120 mg / mL and 40 mg / mL, respectively; and the mass ratio of the aerogel to the nano zinc oxide powder is 1:1.

[0018] A further preferred method is to divide the sodium hydroxide solution into three equal portions and add them dropwise in stages while stirring.

[0019] A further preferred method is to soak the wet gel in distilled water for 24 hours, change the water, and repeat the soaking process twice.

[0020] In a further preferred embodiment, the aerogel is crushed and placed at both ends of a crucible along with nano-zinc oxide powder. The crucible is then covered and transferred to a tube furnace under activated carbon protection. Under a nitrogen atmosphere, the temperature is increased to 450–500°C at a rate of 15–20°C / min and held for 60–80 minutes. The temperature is then increased to 750–800°C at a rate of 6–8°C / min and held for 70–90 minutes. The mixture is then allowed to cool naturally to room temperature. The amount of activated carbon used is 100–120 times the mass of the aerogel.

[0021] The preferred surface treatment method for the nano-zinc oxide graphene composite material is as follows:

[0022] (A) First, cetyltrimethylammonium bromide and polyvinylpyrrolidone are stirred and dispersed in deionized water, then nano zinc oxide graphene composite material is added, mixed and ball-milled to obtain ball-milled slurry;

[0023] (B) Then the ball mill slurry is stirred and dispersed in anhydrous ethanol, concentrated ammonia (mass concentration 22-25%) is added, and stirred until well mixed to obtain a mixture;

[0024] (C) Add tetraethyl orthosilicate ethanol solution dropwise to the mixture, stir at room temperature, filter to collect the solid, wash with anhydrous ethanol to obtain the intermediate product;

[0025] (D) Finally, the intermediate product was stirred and dispersed in anhydrous ethanol, 3-aminopropyltrihydroxysilane was added, and the mixture was heated to reflux and kept at the reflux temperature for 3-4 hours. The solid was then filtered, washed, and dried to obtain the surface-modified composite material.

[0026] Further preferably, in step (A), the mass ratio of hexadecyltrimethylammonium bromide, polyvinylpyrrolidone, deionized water, and nano-zinc oxide graphene composite material is 1:1:10:20; in step (B), the volume ratio of ball milling slurry, anhydrous ethanol, and concentrated ammonia is 1g:10mL:1.2mL; in step (C), the volume ratio of the mixture to tetraethyl orthosilicate ethanol solution is 6:1, and the tetraethyl orthosilicate ethanol solution is obtained by mixing tetraethyl orthosilicate and anhydrous ethanol at a volume ratio of 3:5; in step (D), the mass ratio of intermediate product, anhydrous ethanol, and 3-aminopropyltrihydroxysilane is 1:6:0.02.

[0027] Preferably, in step (1), the mass ratio of styrene monomer, initiator, dispersant aqueous solution, and foaming agent is 10:0.09-0.1:200-210:0.009-0.01; the dispersant aqueous solution is obtained by stirring and dispersing magnesium sulfate, sodium dodecylbenzene sulfonate, and polyvinyl alcohol in deionized water, and the mass ratio of magnesium sulfate, sodium dodecylbenzene sulfonate, polyvinyl alcohol, and deionized water is 0.1:50-52:0.04-0.05:0.06-0.07.

[0028] Preferably, in step (1), the initiator is obtained by mixing tert-butyl peroxide and benzoyl peroxide in equal mass.

[0029] Preferably, in step (2), the heating conditions are as follows: first, the temperature is increased to 90-100℃ at 12-15℃ / min and held for 30-40 minutes; then, the temperature is increased to 135-145℃ at 8-10℃ / min and held for 50-60 minutes; finally, the temperature is increased to 160-170℃ at 5-6℃ / min and held for 100-120 minutes.

[0030] Preferably, in step (3), the steam heating pre-foaming conditions are: 90-110℃ for 2-3 minutes; ventilated curing at 40-50℃ for 8-10 days; molding in a mold using steam at 90-110℃ for 2-3 minutes and then cooling.

[0031] A high-performance foam insulation material is obtained through the aforementioned preparation method.

[0032] The beneficial effects of this invention are:

[0033] This invention discloses a high-performance foam insulation material and its preparation method. First, styrene monomer and an initiator are added to an aqueous dispersant solution, followed by the addition of a foaming agent. The mixture is stirred and stirred until homogeneous, yielding a premixed solution. The premixed solution is then heated and cooled to 35–40°C with stirring. Stirring is stopped, the solid is filtered, and the solid is washed with water to obtain expandable polystyrene beads. Finally, the expandable polystyrene beads are pre-foamed by steam heating, cured, molded, and demolded to obtain the final product. This invention offers a simple preparation method and improves the performance of the foam insulation material through the use of a specific inorganic foaming agent.

[0034] The foaming agent is prepared as follows: first, a nano-zinc oxide sol is prepared using zinc salt and polyethylene glycol 400 as raw materials; then, mesoporous zinc oxide is added to the nano-zinc oxide sol and stirred until homogeneous to obtain a premix; next, the nano-zinc oxide graphene composite material is surface-treated sequentially with tetraethyl orthosilicate ethanol solution and 3-aminopropyltrihydroxysilane to obtain a surface-modified composite material; finally, the surface-modified composite material and bicarbonate are added to the premix and stirred until homogeneous. This foaming agent mainly comprises bicarbonate, surface-modified composite material, and zinc oxide, exhibiting good dispersibility in the system and excellent foaming effect.

[0035] Zinc oxide is composed of mesoporous zinc oxide and nano-zinc oxide. Mesoporous zinc oxide has a hollow structure with a mesoporous surface, resulting in a large specific surface area. When combined with nano-zinc oxide, the specific surface area is further increased, providing more active sites and improving the foaming effect. The core of the surface-modified composite material is a nano-zinc oxide graphene composite material, which enriches the particle size distribution, optimizes the cell structure, and further improves the foaming effect. Detailed Implementation

[0036] The present invention will be further described below with reference to embodiments. It should be noted that the following description is only for explaining the present invention and does not limit its content.

[0037] Example 1:

[0038] A method for preparing a high-performance foam insulation material includes the following steps:

[0039] (1) First, add styrene monomer and initiator to the dispersant aqueous solution, then add foaming agent, stir and mix well to obtain premixed liquid;

[0040] The mass ratio of styrene monomer, initiator, dispersant aqueous solution, and foaming agent is 10:0.09:200:0.009; the dispersant aqueous solution is obtained by stirring and dispersing magnesium sulfate, sodium dodecylbenzene sulfonate, and polyvinyl alcohol in deionized water, and the mass ratio of magnesium sulfate, sodium dodecylbenzene sulfonate, polyvinyl alcohol, and deionized water is 0.1:50:0.04:0.06.

[0041] The initiator is obtained by mixing tert-butyl peroxide and benzoyl peroxide in equal mass.

[0042] (2) Then the premixed liquid is heated and cooled to 35°C by stirring. Stirring is stopped, the solid is filtered and washed with water to obtain expandable polystyrene beads.

[0043] The heat treatment conditions are as follows: first, heat to 90℃ at 12℃ / min and hold for 30 minutes; then heat to 135℃ at 8℃ / min and hold for 50 minutes; finally, heat to 160℃ at 5℃ / min and hold for 100 minutes.

[0044] (3) Finally, the expandable polystyrene beads are pre-foamed by steam heating, cured, molded, and demolded to obtain the foam insulation material.

[0045] The steam heating pre-foaming conditions are: 90℃ for 2 minutes; ventilated curing at 40℃ for 8 days; molding in a mold using 90℃ steam (2 minutes) and cooling.

[0046] The foaming agent is prepared as follows: first, a nano zinc oxide sol is prepared using zinc salt and polyethylene glycol 400 as raw materials; then, mesoporous zinc oxide is added to the nano zinc oxide sol and stirred until homogeneous to obtain a premix; then, the nano zinc oxide graphene composite material is surface-treated sequentially with tetraethyl orthosilicate ethanol solution and 3-aminopropyltrihydroxysilane to obtain a surface-modified composite material; finally, the surface-modified composite material and bicarbonate are added to the premix and stirred until homogeneous.

[0047] The preparation method of the nano zinc oxide sol is as follows: add zinc salt to polyethylene glycol 400, heat at 180°C for 30 minutes, cool naturally to 30°C, centrifuge and take the supernatant to obtain the sol; wherein, the ratio of zinc salt to polyethylene glycol 400 is 2 mmol: 40 mL, and the zinc salt is zinc nitrate.

[0048] The mass ratio of nano zinc oxide sol, mesoporous zinc oxide, surface-modified composite material, and bicarbonate is 10:2:2:3; the bicarbonate is sodium bicarbonate.

[0049] Mesoporous zinc oxide is prepared by the following method: P123 (polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer) is first dispersed in a 70% ethanol aqueous solution by stirring, then zinc chloride and triethanolamine are added, and the mixture is stirred for 6 hours. The mixture is then transferred to a reaction vessel and hydrothermally reacted at 100°C for 12 hours. The precipitate is then collected by centrifugation, washed with water, and dried to obtain the final product.

[0050] The ratio of P123, ethanol aqueous solution, zinc chloride, and triethanolamine is 0.3 mmol: 100 mL: 0.3 mmol: 0.5 mL.

[0051] The nano-zinc oxide graphene composite material was prepared by the following method: First, an aqueous solution of graphene oxide and an aqueous solution of vitamin C were mixed evenly and heated at 80°C for 3 hours to achieve gelation, and the wet gel was collected; then, the wet gel was soaked in distilled water to remove the residual vitamin C aqueous solution, and then freeze-dried under vacuum to obtain an aerogel; then, sodium hydroxide solution was added dropwise to zinc acetate solution, stirred and mixed evenly, and vacuum filtered to obtain zinc hydroxide powder, which was then heat-treated to obtain nano-zinc oxide powder; finally, the aerogel and nano-zinc oxide powder were transferred to a tube furnace and calcined at high temperature under a nitrogen atmosphere to obtain the final product.

[0052] The volume ratio of graphene oxide aqueous solution to vitamin C aqueous solution was 1.5:1, and their concentrations were 2 mg / mL and 100 mg / mL, respectively; the volume ratio of zinc acetate solution to sodium hydroxide solution was 1:1.8, and their concentrations were 120 mg / mL and 40 mg / mL, respectively; the mass ratio of aerogel to nano zinc oxide powder was 1:1.

[0053] Divide the sodium hydroxide solution into three equal portions and add them dropwise while stirring.

[0054] The method for soaking in distilled water is as follows: completely immerse the wet gel in distilled water, soak for 24 hours, change the water, and repeat the soaking twice.

[0055] After crushing the aerogel, place it and the nano zinc oxide powder at opposite ends of a crucible, cover and transfer to a tube furnace. Protect with activated carbon and heat to 450°C at 15°C / min under a nitrogen atmosphere. Hold for 60 minutes, then heat to 750°C at 6°C / min and hold for 70 minutes. Allow to cool naturally to room temperature. The amount of activated carbon used is 100 times the mass of the aerogel.

[0056] The surface treatment methods for nano-zinc oxide graphene composite materials are as follows:

[0057] (A) First, cetyltrimethylammonium bromide and polyvinylpyrrolidone are stirred and dispersed in deionized water, then nano zinc oxide graphene composite material is added, mixed and ball-milled to obtain ball-milled slurry;

[0058] (B) Then the ball mill slurry is stirred and dispersed in anhydrous ethanol, concentrated ammonia (22% by mass) is added, and stirred until well mixed to obtain a mixture;

[0059] (C) Add tetraethyl orthosilicate ethanol solution dropwise to the mixture, stir at room temperature, filter to collect the solid, wash with anhydrous ethanol to obtain the intermediate product;

[0060] (D) Finally, the intermediate product was stirred and dispersed in anhydrous ethanol, 3-aminopropyltrihydroxysilane was added, and the mixture was heated to reflux and kept under reflux for 3 hours. The solid was then filtered, washed, and dried to obtain the surface-modified composite material.

[0061] In step (A), the mass ratio of hexadecyltrimethylammonium bromide, polyvinylpyrrolidone, deionized water, and nano-zinc oxide graphene composite material is 1:1:10:20; in step (B), the volume ratio of ball milling slurry, anhydrous ethanol, and concentrated ammonia is 1g:10mL:1.2mL; in step (C), the volume ratio of the mixture to tetraethyl orthosilicate ethanol solution is 6:1, and the tetraethyl orthosilicate ethanol solution is obtained by mixing tetraethyl orthosilicate and anhydrous ethanol at a volume ratio of 3:5; in step (D), the mass ratio of intermediate product, anhydrous ethanol, and 3-aminopropyltrihydroxysilane is 1:6:0.02.

[0062] Example 2:

[0063] A method for preparing a high-performance foam insulation material includes the following steps:

[0064] (1) First, add styrene monomer and initiator to the dispersant aqueous solution, then add foaming agent, stir and mix well to obtain premixed liquid;

[0065] The mass ratio of styrene monomer, initiator, dispersant aqueous solution, and foaming agent is 10:0.1:210:0.01; the dispersant aqueous solution is obtained by stirring and dispersing magnesium sulfate, sodium dodecylbenzene sulfonate, and polyvinyl alcohol in deionized water, and the mass ratio of magnesium sulfate, sodium dodecylbenzene sulfonate, polyvinyl alcohol, and deionized water is 0.1:52:0.05:0.07.

[0066] The initiator is obtained by mixing tert-butyl peroxide and benzoyl peroxide in equal mass.

[0067] (2) Then the premixed liquid is heated and cooled to 40°C by stirring. Stirring is stopped, the solid is filtered and washed with water to obtain expandable polystyrene beads.

[0068] The heat treatment conditions are as follows: first, heat to 100℃ at 15℃ / min and hold for 40 minutes; then heat to 145℃ at 10℃ / min and hold for 60 minutes; finally, heat to 170℃ at 6℃ / min and hold for 120 minutes.

[0069] (3) Finally, the expandable polystyrene beads are pre-foamed by steam heating, cured, molded, and demolded to obtain the foam insulation material.

[0070] The steam heating pre-foaming conditions are: 110℃ for 3 minutes; ventilated curing at 50℃ for 10 days; molding in a mold using 110℃ steam for 3 minutes and then cooling.

[0071] The foaming agent is prepared as follows: first, a nano zinc oxide sol is prepared using zinc salt and polyethylene glycol 400 as raw materials; then, mesoporous zinc oxide is added to the nano zinc oxide sol and stirred until homogeneous to obtain a premix; then, the nano zinc oxide graphene composite material is surface-treated sequentially with tetraethyl orthosilicate ethanol solution and 3-aminopropyltrihydroxysilane to obtain a surface-modified composite material; finally, the surface-modified composite material and bicarbonate are added to the premix and stirred until homogeneous.

[0072] The preparation method of the nano zinc oxide sol is as follows: add zinc salt to polyethylene glycol 400, heat at 200°C for 40 minutes, cool naturally to 40°C, centrifuge and take the supernatant to obtain the sol; wherein, the ratio of zinc salt to polyethylene glycol 400 is 3 mmol: 50 mL, and the zinc salt is zinc chloride.

[0073] The mass ratio of nano zinc oxide sol, mesoporous zinc oxide, surface-modified composite material, and bicarbonate is 10:3:3:4; the bicarbonate is potassium bicarbonate.

[0074] Mesoporous zinc oxide is prepared by the following method: P123 (polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer) is first dispersed in an 80% ethanol aqueous solution by stirring, then zinc chloride and triethanolamine are added, and the mixture is stirred for 7 hours. The mixture is then transferred to a reaction vessel and hydrothermally reacted at 120°C for 15 hours. The precipitate is then collected by centrifugation, washed with water, and dried to obtain the final product.

[0075] The ratio of P123, ethanol aqueous solution, zinc chloride, and triethanolamine is 0.4 mmol: 100 mL: 0.4 mmol: 0.6 mL.

[0076] The nano-zinc oxide graphene composite material was prepared by the following method: First, an aqueous solution of graphene oxide and an aqueous solution of vitamin C were mixed evenly and heated at 90°C for 4 hours to achieve gelation, and the wet gel was collected; then, the wet gel was soaked in distilled water to remove the residual vitamin C aqueous solution, and then freeze-dried under vacuum to obtain an aerogel; then, sodium hydroxide solution was added dropwise to zinc acetate solution, stirred and mixed evenly, and vacuum filtered to obtain zinc hydroxide powder, which was then heat-treated to obtain nano-zinc oxide powder; finally, the aerogel and nano-zinc oxide powder were transferred to a tube furnace and calcined at high temperature under a nitrogen atmosphere to obtain the final product.

[0077] The volume ratio of graphene oxide aqueous solution to vitamin C aqueous solution was 2:1, and their concentrations were 2 mg / mL and 100 mg / mL, respectively; the volume ratio of zinc acetate solution to sodium hydroxide solution was 1:2, and their concentrations were 120 mg / mL and 40 mg / mL, respectively; the mass ratio of aerogel to nano zinc oxide powder was 1:1.

[0078] Divide the sodium hydroxide solution into three equal portions and add them dropwise while stirring.

[0079] The method for soaking in distilled water is as follows: completely immerse the wet gel in distilled water, soak for 24 hours, change the water, and repeat the soaking twice.

[0080] After crushing the aerogel, place it and the nano zinc oxide powder at opposite ends of a crucible, cover and transfer to a tube furnace. Protect with activated carbon and heat to 500°C at 20°C / min under a nitrogen atmosphere. Hold for 80 minutes, then heat to 800°C at 8°C / min and hold for 90 minutes. Allow to cool naturally to room temperature. The amount of activated carbon used is 120 times the mass of the aerogel.

[0081] The surface treatment methods for nano-zinc oxide graphene composite materials are as follows:

[0082] (A) First, cetyltrimethylammonium bromide and polyvinylpyrrolidone are stirred and dispersed in deionized water, then nano zinc oxide graphene composite material is added, mixed and ball-milled to obtain ball-milled slurry;

[0083] (B) Then the ball mill slurry is stirred and dispersed in anhydrous ethanol, concentrated ammonia (25% by mass) is added, and stirred until well mixed to obtain a mixture;

[0084] (C) Add tetraethyl orthosilicate ethanol solution dropwise to the mixture, stir at room temperature, filter to collect the solid, wash with anhydrous ethanol to obtain the intermediate product;

[0085] (D) Finally, the intermediate product was stirred and dispersed in anhydrous ethanol, 3-aminopropyltrihydroxysilane was added, and the mixture was heated to reflux and kept at the reflux temperature for 4 hours. The solid was then filtered, washed, and dried to obtain the surface-modified composite material.

[0086] In step (A), the mass ratio of hexadecyltrimethylammonium bromide, polyvinylpyrrolidone, deionized water, and nano-zinc oxide graphene composite material is 1:1:10:20; in step (B), the volume ratio of ball milling slurry, anhydrous ethanol, and concentrated ammonia is 1g:10mL:1.2mL; in step (C), the volume ratio of the mixture to tetraethyl orthosilicate ethanol solution is 6:1, and the tetraethyl orthosilicate ethanol solution is obtained by mixing tetraethyl orthosilicate and anhydrous ethanol at a volume ratio of 3:5; in step (D), the mass ratio of intermediate product, anhydrous ethanol, and 3-aminopropyltrihydroxysilane is 1:6:0.02.

[0087] Example 3:

[0088] A method for preparing a high-performance foam insulation material includes the following steps:

[0089] (1) First, add styrene monomer and initiator to the dispersant aqueous solution, then add foaming agent, stir and mix well to obtain premixed liquid;

[0090] The mass ratio of styrene monomer, initiator, dispersant aqueous solution, and foaming agent is 10:0.09:205:0.01; the dispersant aqueous solution is obtained by stirring and dispersing magnesium sulfate, sodium dodecylbenzene sulfonate, and polyvinyl alcohol in deionized water, and the mass ratio of magnesium sulfate, sodium dodecylbenzene sulfonate, polyvinyl alcohol, and deionized water is 0.1:51:0.04:0.07.

[0091] The initiator is obtained by mixing tert-butyl peroxide and benzoyl peroxide in equal mass.

[0092] (2) Then the premixed liquid is heated and cooled to 38°C by stirring. Stirring is stopped, the solid is filtered and washed with water to obtain expandable polystyrene beads.

[0093] The heat treatment conditions are as follows: first, heat up to 95℃ at 13℃ / min and hold for 35 minutes; then heat up to 140℃ at 9℃ / min and hold for 55 minutes; finally, heat up to 165℃ at 5℃ / min and hold for 110 minutes.

[0094] (3) Finally, the expandable polystyrene beads are pre-foamed by steam heating, cured, molded, and demolded to obtain the foam insulation material.

[0095] The steam heating pre-foaming conditions are: 100℃ for 2.5 minutes; ventilated curing at 45℃ for 9 days; molding in a mold using 100℃ steam (2.5 minutes) and cooling.

[0096] The foaming agent is prepared as follows: first, a nano zinc oxide sol is prepared using zinc salt and polyethylene glycol 400 as raw materials; then, mesoporous zinc oxide is added to the nano zinc oxide sol and stirred until homogeneous to obtain a premix; then, the nano zinc oxide graphene composite material is surface-treated sequentially with tetraethyl orthosilicate ethanol solution and 3-aminopropyltrihydroxysilane to obtain a surface-modified composite material; finally, the surface-modified composite material and bicarbonate are added to the premix and stirred until homogeneous.

[0097] The preparation method of the nano zinc oxide sol is as follows: add zinc salt to polyethylene glycol 400, heat at 190°C for 35 minutes, cool naturally to 35°C, centrifuge and take the supernatant to obtain the sol; wherein, the ratio of zinc salt to polyethylene glycol 400 is 2 mmol: 45 mL, and the zinc salt is zinc chloride.

[0098] The mass ratio of nano zinc oxide sol, mesoporous zinc oxide, surface-modified composite material, and bicarbonate is 10:2.5:2.5:3; the bicarbonate is ammonium bicarbonate.

[0099] Mesoporous zinc oxide is prepared by the following method: First, P123 (polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer) is stirred and dispersed in a 75% ethanol aqueous solution. Then, zinc chloride and triethanolamine are added, and the mixture is stirred for 6 hours. The mixture is then transferred to a reaction vessel and hydrothermally reacted at 110°C for 13 hours. The precipitate is then collected by centrifugation, washed with water, and dried to obtain the final product.

[0100] The ratio of P123, ethanol aqueous solution, zinc chloride, and triethanolamine is 0.35 mmol: 100 mL: 0.3 mmol: 0.6 mL.

[0101] The nano-zinc oxide graphene composite material was prepared by the following method: First, an aqueous solution of graphene oxide and an aqueous solution of vitamin C were mixed evenly and heated at 85°C for 3 hours to achieve gelation, and the wet gel was collected; then, the wet gel was soaked in distilled water to remove the residual vitamin C aqueous solution, and then freeze-dried under vacuum to obtain an aerogel; then, sodium hydroxide solution was added dropwise to zinc acetate solution, stirred and mixed evenly, and vacuum filtered to obtain zinc hydroxide powder, which was then heat-treated to obtain nano-zinc oxide powder; finally, the aerogel and nano-zinc oxide powder were transferred to a tube furnace and calcined at high temperature under a nitrogen atmosphere to obtain the final product.

[0102] The volume ratio of graphene oxide aqueous solution to vitamin C aqueous solution was 1.8:1, and their concentrations were 2 mg / mL and 100 mg / mL, respectively; the volume ratio of zinc acetate solution to sodium hydroxide solution was 1:1.9, and their concentrations were 120 mg / mL and 40 mg / mL, respectively; the mass ratio of aerogel to nano zinc oxide powder was 1:1.

[0103] Divide the sodium hydroxide solution into three equal portions and add them dropwise while stirring.

[0104] The method for soaking in distilled water is as follows: completely immerse the wet gel in distilled water, soak for 24 hours, change the water, and repeat the soaking twice.

[0105] After crushing the aerogel, place it and the nano zinc oxide powder at opposite ends of a crucible, cover and transfer to a tube furnace. Protect with activated carbon and heat to 480°C at 18°C / min under a nitrogen atmosphere. Hold for 70 minutes, then heat to 780°C at 7°C / min and hold for 80 minutes. Allow to cool naturally to room temperature. The amount of activated carbon used is 110 times the mass of the aerogel.

[0106] The surface treatment methods for nano-zinc oxide graphene composite materials are as follows:

[0107] (A) First, cetyltrimethylammonium bromide and polyvinylpyrrolidone are stirred and dispersed in deionized water, then nano zinc oxide graphene composite material is added, mixed and ball-milled to obtain ball-milled slurry;

[0108] (B) Then the ball mill slurry is stirred and dispersed in anhydrous ethanol, concentrated ammonia (23% by mass) is added, and stirred until well mixed to obtain a mixture;

[0109] (C) Add tetraethyl orthosilicate ethanol solution dropwise to the mixture, stir at room temperature, filter to collect the solid, wash with anhydrous ethanol to obtain the intermediate product;

[0110] (D) Finally, the intermediate product was stirred and dispersed in anhydrous ethanol, 3-aminopropyltrihydroxysilane was added, and the mixture was heated to reflux and kept at the reflux temperature for 3-4 hours. The solid was then filtered, washed, and dried to obtain the surface-modified composite material.

[0111] In step (A), the mass ratio of hexadecyltrimethylammonium bromide, polyvinylpyrrolidone, deionized water, and nano-zinc oxide graphene composite material is 1:1:10:20; in step (B), the volume ratio of ball milling slurry, anhydrous ethanol, and concentrated ammonia is 1g:10mL:1.2mL; in step (C), the volume ratio of the mixture to tetraethyl orthosilicate ethanol solution is 6:1, and the tetraethyl orthosilicate ethanol solution is obtained by mixing tetraethyl orthosilicate and anhydrous ethanol at a volume ratio of 3:5; in step (D), the mass ratio of intermediate product, anhydrous ethanol, and 3-aminopropyltrihydroxysilane is 1:6:0.02.

[0112] Comparative Example 1

[0113] Mesoporous zinc oxide is omitted when preparing the foaming agent;

[0114] The rest is the same as in Example 1.

[0115] Comparative Example 2

[0116] Surface-modified composite materials are omitted during the preparation of the foaming agent;

[0117] The rest is the same as in Example 1.

[0118] Test case

[0119] The performance of the foam insulation materials obtained in Examples 1-3 and Comparative Examples 1 and 2 were tested, specifically including:

[0120] 1. Thermal conductivity (20℃): Tested using a thermal conductivity tester, employing the transient plane heat source method, model ZHDL-S, brand Zhonghang Dingli.

[0121] 2. Tensile strength: Tested in accordance with GB / T9641-2025 "Determination of tensile properties of rigid foamed plastics".

[0122] The test results are shown in Table 1.

[0123] Table 1. Performance Testing of Foam Insulation Materials

[0124] Example 1 0.031 275 Example 2 0.031 280 Example 3 0.030 280 Comparative Example 1 0.040 154 Comparative Example 2 0.041 127

[0125] As shown in Table 1, the foam insulation materials obtained in Examples 1 to 3 have low thermal conductivity, high tensile strength, and excellent performance.

[0126] Comparative Example 1 omitted mesoporous zinc oxide when preparing the foaming agent, and Comparative Example 2 omitted surface-modified composite material when preparing the foaming agent. The thermal conductivity increased significantly and the tensile strength decreased. This shows that the foaming agent composition of this application synergistically improves the foaming effect, improves the thermal insulation performance, and has a uniform and fine cell structure, thus improving the mechanical properties.

[0127] While the specific embodiments of the present invention have been described above, they are not intended to limit the scope of protection of the present invention. Based on the technical solutions of the present invention, various modifications or variations that can be made by those skilled in the art without creative effort are still within the scope of protection of the present invention.

Claims

1. A method for preparing a high-performance foam insulation material, characterized in that, Includes the following steps: (1) First, add styrene monomer and initiator to the dispersant aqueous solution, then add foaming agent, stir and mix well to obtain premixed liquid; (2) Then heat the premixed liquid, stir and cool it down to 35-40°C, stop stirring, filter to take the solid, wash with water, and obtain expandable polystyrene beads. (3) Finally, the expandable polystyrene beads are pre-foamed by steam heating, cured, molded, and demolded to obtain the foam insulation material. The foaming agent is prepared as follows: first, a nano zinc oxide sol is prepared using zinc salt and polyethylene glycol 400 as raw materials; then, mesoporous zinc oxide is added to the nano zinc oxide sol and stirred until homogeneous to obtain a premix; then, the nano zinc oxide graphene composite material is surface-treated sequentially with tetraethyl orthosilicate ethanol solution and 3-aminopropyltrihydroxysilane to obtain a surface-modified composite material; finally, the surface-modified composite material and bicarbonate are added to the premix and stirred until homogeneous.

2. The preparation method according to claim 1, characterized in that, The preparation method of the nano zinc oxide sol is as follows: add zinc salt to polyethylene glycol 400, heat at 180-200℃ for 30-40 minutes, cool naturally to 30-40℃, centrifuge and collect the supernatant to obtain the sol; wherein, the ratio of zinc salt to polyethylene glycol 400 is 2-3 mmol: 40-50 mL, and the zinc salt is zinc chloride or zinc nitrate.

3. The preparation method according to claim 1, characterized in that, The mass ratio of nano zinc oxide sol, mesoporous zinc oxide, surface-modified composite material, and bicarbonate is 10:2-3:2-3:3-4; the bicarbonate is selected from any one or more of sodium bicarbonate, potassium bicarbonate, and ammonium bicarbonate.

4. The preparation method according to claim 1, characterized in that, The mesoporous zinc oxide is prepared by the following method: P123 is first dispersed in an aqueous ethanol solution with a volume concentration of 70-80%, then zinc chloride and triethanolamine are added, and the mixture is stirred for 6-7 hours. The mixture is then transferred to a reaction vessel and subjected to hydrothermal reaction at 100-120°C for 12-15 hours. The precipitate is then collected by centrifugation, washed with water, and dried to obtain the final product.

5. The preparation method according to claim 1, characterized in that, The nano-zinc oxide graphene composite material is prepared by the following method: First, an aqueous solution of graphene oxide and an aqueous solution of vitamin C are mixed evenly and heated at 80-90°C for 3-4 hours to achieve gelation, and the wet gel is collected; then, the wet gel is soaked in distilled water to remove residual vitamin C aqueous solution, and then freeze-dried under vacuum to obtain an aerogel; then, sodium hydroxide solution is added dropwise to zinc acetate solution, stirred and mixed evenly, and vacuum filtered to obtain zinc hydroxide powder, which is then heat-treated to obtain nano-zinc oxide powder; finally, the aerogel and nano-zinc oxide powder are transferred to a tube furnace and calcined at high temperature under a nitrogen atmosphere to obtain the final product.

6. The preparation method according to claim 1, characterized in that, The surface treatment methods for nano-zinc oxide graphene composite materials are as follows: (A) First, cetyltrimethylammonium bromide and polyvinylpyrrolidone are stirred and dispersed in deionized water, then nano zinc oxide graphene composite material is added, mixed and ball-milled to obtain ball-milled slurry; (B) Then the ball mill slurry is stirred and dispersed in anhydrous ethanol, concentrated ammonia is added, and the mixture is stirred until homogeneous to obtain a mixture; (C) Add tetraethyl orthosilicate ethanol solution dropwise to the mixture, stir at room temperature, filter to collect the solid, wash with anhydrous ethanol to obtain the intermediate product; (D) Finally, the intermediate product was stirred and dispersed in anhydrous ethanol, 3-aminopropyltrihydroxysilane was added, and the mixture was heated to reflux and kept at the reflux temperature for 3-4 hours. The solid was then filtered, washed, and dried to obtain the surface-modified composite material.

7. The preparation method according to claim 1, characterized in that, In step (1), the mass ratio of styrene monomer, initiator, dispersant aqueous solution, and foaming agent is 10:0.09~0.1:200~210:0.009~0.01; the dispersant aqueous solution is obtained by stirring and dispersing magnesium sulfate, sodium dodecylbenzene sulfonate, and polyvinyl alcohol in deionized water, and the mass ratio of magnesium sulfate, sodium dodecylbenzene sulfonate, polyvinyl alcohol, and deionized water is 0.1:50~52:0.04~0.05:0.06~0.

07.

8. The preparation method according to claim 1, characterized in that, In step (2), the heating conditions are as follows: first, heat the temperature to 90-100℃ at 12-15℃ / min and hold for 30-40 minutes; then heat the temperature to 135-145℃ at 8-10℃ / min and hold for 50-60 minutes; finally, heat the temperature to 160-170℃ at 5-6℃ / min and hold for 100-120 minutes.

9. The preparation method according to claim 1, characterized in that, In step (3), the steam heating pre-foaming conditions are: 90-110℃ for 2-3 minutes; ventilated curing at 40-50℃ for 8-10 days; molding in the mold using steam at 90-110℃ for 2-3 minutes and then cooling.

10. A high-performance foam insulation material, characterized in that, It is obtained by the preparation method described in any one of claims 1 to 9.